Engineering Zymomonas mobilis for the production of xylonic acid from sugarcane bagasse hydrolysate - Herrera, Christiane Ribeiro Janner (2021)
Sugarcane bagasse is an agricultural residue rich in xylose, which may be used as a feedstock for the production of high-value-added chemicals, such as xylonic acid, an organic acid listed as one of the top 30 value-added chemicals on a NREL report. Here, Zymomonas mobilis was engineered for the first time to produce xylonic acid from sugarcane bagasse hydrolysate. Seven coding genes for xylose dehydrogenase (XDH) were tested. The expression of XDH gene from Paraburkholderia xenovorans allowed the highest production of xylonic acid (26.17 ± 0.58 g L−1) from 50 g L−1 xylose in shake flasks, with a productivity of 1.85 ± 0.06 g L−1 h −1 and a yield of 1.04 ± 0.04 gAX/gX. Deletion of the xylose reductase gene further increased the production of xylonic acid to 56.44 ± 1.93 g L−1 from 54.27 ± 0.26 g L−1 xylose in a bioreactor. Strain performance was also evaluated in sugarcane bagasse hydrolysate as a cheap feedstock, which resulted in the production of 11.13 g L−1 xylonic acid from 10 g L−1 xylose. The results show that Z. mobilis may be regarded as a potential platform for the production of organic acids from cheap lignocellulosic biomass in the context of biorefineries.